2011
DOI: 10.5551/jat.8144
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Dimethylarginine Levels are Associated with Adverse Clinical Outcome After Stroke

Abstract: Aim: Increased levels of asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase, have been observed in patients with cardiovascular risk factors and atherosclerosis and in patients with a history of stroke. The role of ADMA and its analogue symmetric dimethylarginine (SDMA) in acute ischemic stroke is yet unclear. We hypothesized that plasma dimethylarginine levels increase in the hyper-acute phase after ischemic stroke and that their time course is related to stroke outcome. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 35 publications
(36 reference statements)
1
51
1
Order By: Relevance
“…In a clinical study of patients with aneurysmal SAH, a strong correlation between ADMA concentrations in CSF and degree of cerebral vasospasm was found, but ADMA concentrations in serum remained unchanged during the study period [17]. This is in contrast to the rapid increase in plasma concentrations of ADMA after ischemic stroke reported by Worthmann et al [14]. In a small study on patients with SAH caused by aneurysmal bleeding or trauma, increased concentrations of ADMA were shown both in both plasma and CSF [18].…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In a clinical study of patients with aneurysmal SAH, a strong correlation between ADMA concentrations in CSF and degree of cerebral vasospasm was found, but ADMA concentrations in serum remained unchanged during the study period [17]. This is in contrast to the rapid increase in plasma concentrations of ADMA after ischemic stroke reported by Worthmann et al [14]. In a small study on patients with SAH caused by aneurysmal bleeding or trauma, increased concentrations of ADMA were shown both in both plasma and CSF [18].…”
Section: Introductioncontrasting
confidence: 54%
“…A massive systemic inflammatory response is triggered by SAH and induces an increase in inflammatory markers such as C-Reactive Protein (CRP) [12]. High ADMA concentrations after ischemic stroke has been associated to un-favourable outcome, and elevated concentrations of ADMA can be lowered by anti-inflammatory treatment with statins [13,14]. However, the timing of ADMA and CRP as markers for inflammatory response after SAH remains to be elucidated [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that higher SDMA levels in the cerebrospinal fluid were correlated with a poor outcome at 3 months after stroke onset. 4 Worthmann et al 5 demonstrated that an increase of both plasma ADMA and SDMA levels within the first 72 hours after the onset of ischemic stroke may predict a poor outcome. In this context, it is strongly suggested that both ADMA and SDMA could be the biomarkers referring to endothelial dysfunction and disturbed cerebrovascular circulation.…”
Section: To the Editormentioning
confidence: 99%
“…This is in line with previous data from a clinical stroke study that did not include subgroup analysis for acute stroke treatment. 9 Considering data from animal models and endothelial cell cultures, we hypothesized that elevation of ADMA levels might be pronounced in patients who received EPO or EPO+rtPA compared with those with placebo. 15,16 However, we could not prove this hypothesis.…”
Section: No Augmentation Of Adma Increase By Treatment With Epo In Acmentioning
confidence: 99%
“…ADMA increase after acute stroke is associated with adverse outcome. [9][10][11] It is suggested that ADMA might significantly contribute to brain injury after stroke by decreasing cerebral perfusion and triggering oxidative stress and inflammation. [12][13][14] Treatment with EPO increased ADMA levels in both, cell cultures and experimental animals.…”
mentioning
confidence: 99%